Designing The Elderly Janger Dance Model In Tonja Village Denpasar - Ni Made Ruastiti (Institut Seni Indonesia Denpasar, 2016)
The Elderly ./anger Dance (EJD) is a type of performing that particularly designed for elderly people, initially from its choreography, costume and makeup, or even its musical accompaniment. This performing is signiï¬cantly created as those elderly people are offered a performing art model that is not suitable to their physical condition.Several problems arose during its process of creation, choreography, and the tempo, costume makeup, duration and their condition while performing the dance. It results to their disinterest on art participation. Therefore, this research is aimed at solving the problem on the improper of the art-performing model for those elderly people. This research is conducted in Tonja village, Denpasar by considering the adequateness of number and art potential of this area.The designing ofthis performing model is carried out through applying the participatory-implemented method. It focuses on the cooperation between researchers and the related parties started from socialization-planned model, implementation model until the trial model.Based on the whole stages of designing model on EJD, it is produced outputs as follows: EJD Model, activities report, article, lesson module, and HKI. Through this dance creation, those elderly are passionate again to participate on art. Simultaneously, it will affect their health quality improvement through art activity.Keywords: Performing- model design, Choreography, Outlook/make up and costume, musical accompaniment, Elderly Janger Dance (EJD)